Kualitas situs web, kepercayaan, dan loyalitas konsumen Tokopedia - Fanny Suzuda Pohan; Zida Fajar Aulia (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
The purposes of this research are to determine the effect of the website quality on the Tokopedia’s customer trust, and the effect of trust on Tokopedia's customer loyalty. As an independent variable, website quality was reflected by information, security, convenience, comfort, and service. Data was collected using questionnaires on 100 respondents through a non-probability sampling approach. Structural Equation Modeling PLS was used to model testing. The results show that the partial factors of website quality (information and security) have a significant effect on customer trust and trust has a significant effect on Tokopedia's customer loyalty. Implications and suggestions are discussed in the paper.